Impact of climate change on agricultural yield: evidence from Vietnam - Le Thanh Tung; Jan Bentzen (Agricultural and Resource Economics)
Purpose. Climate change is considered as one of the most stressful issues nowadays. This study aims to explore the impact of climate change on agricultural yields in Vietnam, a leading exporter in global agricultural markets.